In vivo Antimalarial Activity of a Labdane Diterpenoid from the Leaves of Otostegia integrifolia Benth. (11th February 2013) - Endale, Abyot; Bisrat, Daniel; Animut, Abebe; Bucar, Franz; Asres, Kaleab
<x xml:space="preserve">Abstract</x> In Ethiopian traditional medicine, the leaves of Otostegia integrifolia Benth. are used for the treatment of several diseases including malaria. In an ongoing search for effective, safe and cheap antimalarial agents from plants, the 80% methanol leaf extract O. integrifolia was tested for its in vivo antimalarial activity, in a 4‐day suppressive assay against Plasmodium berghei. Activity‐guided fractionation of this extract which showed potent antiplasmodial activity resulted in the isolation of a labdane diterpenoid identified as otostegindiol. Otostegindiol displayed a significant (P < 0.001) antimalarial activity at doses of 25, 50 and 100 mg/kg with chemosuppression values of 50.13, 65.58 and 73.16%, respectively. Acute toxicity studies revealed that the crude extract possesses no toxicity in mice up to a maximum dose of 5000 mg/kg suggesting the relative safety of the plant when administered orally. The results of the present study indicate that otostegindiol is among the antimalarial principles in this medicinal plant, and further support claims for the traditional medicinal use of the plant for the treatment of malaria. Copyright © 2013 John Wiley & Sons, Ltd.